Cytotoxicity of Zardaverine in Embryonal Rhabdomyosarcoma from a Costello Syndrome Patient - Cartledge, Donna M.; Robbins, Katherine M.; Drake, Katherine M.; Sternberg, Rachel; Stabley, Deborah L.; Gripp, Karen W.; Kolb, E. Anders; Sol-Church, Katia; Napper, Andrew D. (Frontiers in Oncology, 2017)
Costello syndrome (CS) patients suffer from a very high 10% incidence of embryonal rhabdomyosarcoma (ERMS). As tools to discover targeted therapeutic leads, we used a CS patient-derived ERMS cell line (CS242 ERMS) harboring a homozygous p.G12A mutation in HRAS, and a control cell line derived from the same patient comprising non-malignant CS242 fibroblasts with a heterozygous p.G12A HRAS mutation. A library of 2000 compounds with known pharmacological activities was screened for their effect on CS242 ERMS cell viability. Follow-up testing in a panel of cell lines revealed that various compounds originally developed for other indications were remarkably selective; notably, the phosphodiesterase inhibitor zardaverine was at least 1000-fold more potent in CS242 ERMS than in the patient-matched non-malignant CS242 fibroblasts, other ERMS, or normal fibroblasts. Chronic treatment with zardaverine led to the emergence of resistant cells, consistent with CS242 ERMS comprising a mixed population of cells. Many phosphodiesterase inhibitors in addition to zardaverine were tested on CS242 ERMS, but almost all had no effect, suggesting that phosphodiesterase inhibition alone is not sufficient to cause cell killing. Interestingly, zardaverine and analogs showed a similar cytotoxicity profile in CS242 ERMS and cervical carcinoma-derived HeLa cells, suggesting a mechanism of action common to both cell types that does not require the presence of an HRAS mutation (HeLa contains wild type HRAS). Two recent studies presented possible mechanistic explanations for the cytotoxicity of zardaverine in HeLa cells. One revealed that zardaverine inhibited a HeLa cell-based screen measuring glucocorticoid receptor activation; however, using engineered HeLa cells we ruled out a specific effect of zardaverine on signaling through the glucocorticoid receptor. The second attributed zardaverine toxicity in HeLa cells to promotion of the interaction of phosphodiesterase 3A and the growth regulatory protein Schlafen 12. This work may provide a possible mechanism for zardaverine action in CS242 ERMS, although we have not yet tested this. In conclusion, we have identified zardaverine as a potent cytotoxic agent in a CS-derived ERMS cell line and in HeLa. Although we have ruled out some possibilities, the mechanism of action of zardaverine in CS242 ERMS remains to be determined.